2003
DOI: 10.1002/app.13279
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of water‐dispersed flame‐retardant polyurethane resin using phosphorus‐containing chain extender

Abstract: ABSTRACT:In this research, a flame-retardant water-dispersed polyurethane resin was synthesized through incorporating phosphonate groups into the polyurethane structure in the chain-extension step. A phosphorus-containing reactive flame-retardant compound was synthesized for this purpose. First, bis(4-nitrophenyl)phenyl phosphine oxide was synthesized and then converted to bis(4-amino phenyl)-phenyl phosphine oxide (BAPPO) by reducing its nitro groups into amines. The obtained products were characterized by IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The lower initial decomposition temperatures might have resulted from the catalytic effect of the nanoclays on the fragmentation of the macromolecular chain. The presence of photonic catalytic sites could have catalyzed char crosslinking interactions to form a charred residue, which combined and intercalated with the silicate layers to provide a sort of char–layered‐silicate nanocomposite . The residue at the high temperature increased for Na‐MMT and was replaced by the same amount of o‐MMT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower initial decomposition temperatures might have resulted from the catalytic effect of the nanoclays on the fragmentation of the macromolecular chain. The presence of photonic catalytic sites could have catalyzed char crosslinking interactions to form a charred residue, which combined and intercalated with the silicate layers to provide a sort of char–layered‐silicate nanocomposite . The residue at the high temperature increased for Na‐MMT and was replaced by the same amount of o‐MMT.…”
Section: Resultsmentioning
confidence: 99%
“…However, there has been increasing interest in the use of halogen‐free flame retardant substances. Many more efforts have been made to use phosphorus‐based compounds for flame retardants . Researchers have reported that phosphorus–nitrogen (P–N) flame retardants must cooperate with other synergistic agents to prepare excellent flame‐retarding thermoplastic esters …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incorporation of P-HSi improved mechanical as well as dielectric properties of the CE systems. [142] CONCLUSION Despite the high cost of reactive flame retardants, they were proven to be the most [96] , II-(Bis-4 nitrophenoxy) phenyl Phosphine oxide [74] , III-Neopentyl glycol phosphonyl chloride [79] , IV-Tri(ethyldiamino) phosphate [92] , V-3,9-dichloro-2,4,8-l0 tetraoxa-3,9-diphosphaspiro [5,5]undecane-3,9-dioxide [80] , VI-1-Oxo-4-methoxy-2,6,7-trioxa-1-phosphabicyclo[2,2,2]octane [81] , VII-Tri(Ethyloxyamino) phosphate, VIIITri(acryloxyethyl) phosphate [83] , IX-Tri(Glycidyloxymethylacryloxy) phosphate [56] , X-P-containing triol. [72] Figure 13.…”
Section: Another Polymeric Curing Agent Based On α-Aminophosphinate Wmentioning
confidence: 97%
“…Polat et al synthesized phosphorous containing amine pending group, incorporated during the chain extension stage of synthesis and proven to be excellent flame retardant for aqueous PUs by exhibiting LOI of 27 [74] . In another research work, Phosphorouscontaining aziridine compounds (Fig.…”
Section: Unsaturated Polyestersmentioning
confidence: 99%
“…More particularly, the Polyurethanes containing some phosphorus elements are well documented in the literature. Indeed such Polyurethanes find applications in various domains such as foams [7,8], adhesives coatings [1], automotives [9] and FR polymers, either through an additive or a reactive pathway [10][11][12][13][14][15]. The Polyurethanes are in majority derived from an exothermic reaction between di-isocyanates and hydroxyl-telechelic oligomers [16,17] even if the literature describes other methodologies such as Non Isocyanate Polyurethanes (NIPU) to synthesized from liquid HTNR and demonstrated a higher thermal stability compared to other commercial based analogues [26].…”
Section: Introductionmentioning
confidence: 98%